Level Of Perception Emergency Skills In Youth Red Cross - Suwardianto, Heru (Institut Ilmu Kesehatan STRADA Indonesia, 2018)
Background: The state of emergency at school is a crisis condition of an environmental or individual condition. An emergency situation can happen to anyone, anywhere, anytime. Critical patients are a condition of one or more system organ failures that are irreversible. Purpose : The purpose of this study is to determine the level of perception emergency skills in youth red cross at Senior High School 3 Kediri City. Methods : Research Design was descriptive analitic. The population was the students who are members of the youth red cross at the Senior High School 3 Kediri City. Sample ware 35 respondents based on inclusion and exclusion criteria using purposive sampling. The variable ware skill in performing the act of measurement of blood pressure, pulse, temperature position the victim fainted because of low blood pressure, position the victim fainted because of asthma, open wounds dressing, splinting of extremities injured or fracture, cardiopulmonary resuscitation, removing off helmet and fixation of the neck victims of traffic accidents. Measuring devices using Analog Range Scale (ARS 1-10): Skill. Result : The results showed that the mean score of less than 5 was on the skill lift the victim fainted because of low blood pressure (4.60 ± 2.51), splinting of extremities injured or fracture (4.77 ± 2.52), cardiopulmonary resuscitation, and removing the helmets and fixation of neck victims of traffic accidents (1.63 ± 2.47). The results of the study also found that 8 groups of data had a skewness ratio of -2 / + 2, and a group of non-distributed data on cardiopulmonary resuscitation skills (3.42), and removal of helmets and neck injuries for traffic casualties (4.77 ). Conclusion : Increased preparedness with training is required in schools to reduce the risk of emergency or disaster events